2016
DOI: 10.1111/nyas.13214
|View full text |Cite
|
Sign up to set email alerts
|

Biological and environmental hazards associated with exposure to chemical warfare agents: arsenicals

Abstract: Arsenicals are highly reactive inorganic and organic derivatives of arsenic. These chemicals are very toxic and produce both acute and chronic tissue damage. Based on these observations, and considering the low cost and simple methods of their bulk syntheses, these agents were thought to be appropriate for chemical warfare. Among these, the most known agent synthesized and weaponized during World War I (WWI) is Lewisite. Exposure to Lewisite causes painful inflammatory and blistering responses in the skin, lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 75 publications
(219 reference statements)
0
18
0
Order By: Relevance
“…8 Lewisite can cause lung, liver, kidney, and neuronal damage. 16,17,59 A clear understanding of these effects is currently incomplete because of a lack of suitable experimental animal models. Earlier, we showed that in the highly responsive hairless murine model Ptch1 +/− /SKH-1, systemic injury, such as renal 16 and pulmonary 17 damage, is significantly increased following exposure to lewisite and other arsenicals.…”
Section: Discussionmentioning
confidence: 99%
“…8 Lewisite can cause lung, liver, kidney, and neuronal damage. 16,17,59 A clear understanding of these effects is currently incomplete because of a lack of suitable experimental animal models. Earlier, we showed that in the highly responsive hairless murine model Ptch1 +/− /SKH-1, systemic injury, such as renal 16 and pulmonary 17 damage, is significantly increased following exposure to lewisite and other arsenicals.…”
Section: Discussionmentioning
confidence: 99%
“…These very last warfare agents affect the body by being absorbed into the blood with the routes of inhalation or ingestion. All these As-based agents possess the characteristics of high toxicity, rapidity of action after environmental distribution, and long persistence (Li et al 2016).…”
Section: Arsenic In Chemical Weaponsmentioning
confidence: 99%
“…Arsenicals appear in different states of aggregation and dose-dependently induce acute or chronic cutaneous, ocular, and systemic effects. 75 In a 2010 study, Rubatto et al 76 used rat kidney slices to map arsenic uptake by renal cortex cells, as well as to characterize the impairment of renal function by arsenic accumulation. With regard to other chemicals, recent studies by Carranza-Torres et al 77,78 employed PCTSs to investigate the effects of mercuric chloride (HgCl 2 ).…”
Section: Pcts and Other Weaponizable Chemicalsmentioning
confidence: 99%